2021
DOI: 10.3389/fncel.2021.633280
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-apoptosis Effect of Single Electroacupuncture Treatment via Suppressing Neuronal Autophagy in the Acute Stage of Ischemic Stroke Without Infarct Alleviation

Abstract: The main purpose of the study was to investigate the antiapoptotic effect of electroacupuncture (EA) in the acute stage of ischaemic stroke in rats. The cerebral ischemia model was established by middle cerebral artery occlusion (MCAO)/reperfusion in rats. A single EA treatment was performed at the acute stage of ischaemic stroke. The neurological function, brain water content, apoptotic cell number, and cerebral infarct volume were assessed in stroke rats. The expression of autophagy-related proteins (LC3II/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As shown in the images of H&E staining at 1, 3, and 7 days of RIRI, the two pairs of EA points had a protective impact on the retinal structure and RGC numbers. The results of TUNEL staining revealed that the numbers of apoptotic cells in the two EA groups at 1 and 3 days of RIRI were significantly reduced, consistent with the previous studies (Wang et al, 2020 ; Xing et al, 2021 ). But there was no significant effect on the seventh day of RIRI because the peak of apoptosis had passed, leading to reduction in the number of apoptotic cells in each group.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in the images of H&E staining at 1, 3, and 7 days of RIRI, the two pairs of EA points had a protective impact on the retinal structure and RGC numbers. The results of TUNEL staining revealed that the numbers of apoptotic cells in the two EA groups at 1 and 3 days of RIRI were significantly reduced, consistent with the previous studies (Wang et al, 2020 ; Xing et al, 2021 ). But there was no significant effect on the seventh day of RIRI because the peak of apoptosis had passed, leading to reduction in the number of apoptotic cells in each group.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, EA stimulation of the forepaw in aged rats can substantially increase blood flow in cortical brain tissue [ 29 ]. The best treatment time to improve cerebral circulation should be within 2–3 days after onset, but particularly at 24 h, when apoptosis and brain edema reach a peak after cerebral ischemia-reperfusion injury [ 30 ]. Typically, acupuncture intervention within 2 days of a stroke is the best time to achieve early recovery of motor function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery, rats were fasted for 10 h but allowed to drink. The operation details are illustrated in our previous publications [ 17 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…The neurological deficit assessment was performed in all rats at 2 h or 72 h after MCAO/R in a blind manner. The details are reported in our published articles [ 16 , 60 ].…”
Section: Methodsmentioning
confidence: 99%